Efforts to Improve Children's Literacy through an Islamic Education Approach - Buchari Muslim (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze efforts to improve children's literacy through an Islamic Education approach. The low level of reading interest and literacy skills among children has become a significant challenge in education, requiring approaches that are aligned with religious values. This research employs a qualitative approach with a descriptive study design. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results indicate that the implementation of Islamic values, such as reading the Qur'an, storytelling of exemplary figures, and habituation of character-based literacy, can enhance children's interest and literacy skills. Furthermore, the role of teachers and a supportive religious environment are key factors in the success of Islamic-based literacy programs. Therefore, the Islamic Education approach can serve as a strategic alternative to improve children's literacy in a holistic manner.